Radical Moral Imagination and Moral Luck. (October 2016) - Biss, Mavis
Abstract: To a greater extent than other theorists, Claudia Card in her analysis of moral luck considers the impact of attempts to transform moral meanings on the development of the agent's character and her responsibilities, over time and in relation to other agents. This essay argues that this wider frame of reference captures more of what is at stake in the efforts of those who resist oppression by attempting to implement radically revised meanings.